Evaluation of Friction and Surface Characteristics of Two Types of Self-Ligating Bracket Gate: An In Vitro Study - Hussein A Kanbar; Dina H Obaid; Ali I Ibrahim (Wolters Kluwer Medknow Publications, 2022)
Introduction: Frictional forces generation during orthodontic treatment with fixed appliances impedes appropriate tooth movement; hence, research is ongoing to explore "frictionless" techniques. This in vitro study compares Damon Q and Pactive self-ligating metallic brackets in terms of friction and surface characteristics of the bracket gates when using CuNiTi archwires during leveling and alignment stage and examines the effects of aging conditions on frictional force generation. Methods: A total of 108 metallic self-ligating brackets (Damon Q and Pactive) were investigated for frictional resistance with round 0.014" and rectangular 0.014"∗0.025" CuNiTi archwires post exposure to water storage and acidic attack aging conditions. The bracket gate surface characteristics were evaluated using scanning electron microscope (SEM). Results: There was no statistically significant difference (P > 0.05) in friction generation between the two bracket systems when coupled with 0.014" CuNiTi archwire, but the Pactive brackets yielded significantly higher frictional forces (P < 0.05) when coupled with 0.014"∗0.025" archwire. The SEM findings revealed nonsignificant differences (P > 0.05) between the surface characteristics of the bracket gates. Conclusions: Damon Q brackets generate low frictional forces, suggesting better performance than Pactive brackets during the first phase of orthodontic treatment. A modified scoring system was developed for an objective description of bracket surface characteristics.